SEISMIC VULNERABILITY INDEX MICROZONATION IN MUARA AMAN CITY BASED ON HVSR METHOD - Repal Wijaya Kusuma; Yuni Setyowati; Refrizon; M Farid Farid; Andre Rahmat Al Ansory; Hana Raihana; Nurul ‘Ilmi Rahmawati; Olga Triutami (Jurnal Fisika, 2024)
Muara Aman City has a high frequency of earthquakes. The research aims to map earthquake-prone areas using indicators such as natural/dominant frequency value parameter (f0), amplification factor (A0), and seismic vulnerability index (Kg). Measurements in this study were conducted using a PASI Mod Gemini 2 Sn-1405 seismometer for 30 minutes at 21 measurement points. The data processing results include natural frequency: 0.15-8.59 Hz, amplification factor: 0.97-6.009, and seismic vulnerability index: 0.2-56.3 After obtaining the values of these parameters, a distribution map is created by pairing each parameter value with the coordinates of the research point. Based on the values of these parameters, areas with high seismic vulnerability are found in zones T3, T4, T5, T6, T15, and T16. The research findings can offer valuable insights for both the community and government in implementing strategies to minimize the impact of earthquake damage and losses.